AUTOBIOGRAPHY OF AN AUDIT: TRACING THE ROOTS AND REPERCUSSIONS OF THE HRT-TRANSGENDER DATABASE - Keyes, Os; Austin, Jeanie; Zimmer, Michael (AoIR Selected Papers of Internet Research, 2020)
Focus on the harms in data collection, distribution, and use in sociotechnical systems tends to reify the idea that research conducted by universities and other public-sector parties is both more ethical and more easily lends itself to auditing. This falsely positions data collection and distribution undertaken by public institutions as more available to review and scrutiny. Documenting our attempts to audit the HRT-Transgender Database - a database collected by a public university in the United States - we engage in a critical examination of not only the gaps in IRB coverage of “big data” research, but also the practical limitations and troubles involved in attempting to audit data practices that, on paper, should be highly documented. Drawing from feminist and trans studies critical approaches to information practice, our work brings into frame vital issues that researchers seeking to design oversight mechanisms should address, and begins a conversation about the visceral and often painful work of providing that oversight. This research extends from a review of the limits of IRB oversight to incorporate an interrogation of how technological interventions increase the likelihood of actual and symbolic violence in the lives of transgender people, including those not present in the actual HRT-Transgender Database.